Analisis Yuridis terhadap Penegakan Hukum Pelanggaran Pengujian Kendaraan Bermotor yang Menyebabkan Kecelakaan Lalu Lintas - Pratiwi, Ida Ayu Windhari Kusuma; Pitriyantini, Putu Eka; Dharma, Ida Bagus Wirya; Pramana , I Gusti Agus Yuda Trisna (Universitas Tabanan, 2024)
Transportation is an important infrastructure for the economic life of society, transportation is a means to encourage economic development. Transportation by motorized vehicles often causes problems that can harm passengers. The problem, how is the function of the implementation of motor vehicle testing in an effort to prevent traffic accidents and law enforcement against violations if the owner of motorized transportation does not conduct vehicle testing, Research results: that the function of motor vehicle testing is very decisive in efforts to prevent traffic accidents. Because with the condition of vehicles that meet the technical requirements and roadworthy supported by drivers and road users who are disciplined and aware of the law, the danger of traffic accidents will be prevented or minimized. Law enforcement against violations for motorized transport owners who do not conduct vehicle testing is based on Article 56 of the UULLAJ, if violated shall be punished with a maximum imprisonment of 2 months or a maximum fine of Rp. 2,000,000, - and if the vehicle does not have a proof of passing the test. If the vehicle does not have a test pass mark, it shall be punished with imprisonment of 6 months or a fine of up to Rp. 6,000,000.